The factors that influence the users' adoption and acceptance of cloud computing at University of Technology in South Africa - Lieta, Manche Aloycia (Vaal University of Technology, 2022)
Cloud computing can assist in overcoming the present boundaries in mobile learning (m-learning) regarding the limited processing and storage capabilities of the mobile devices. This way, learning applications can run on students’ mobile devices while the heaviest computing tasks take place in the cloud. For this to happen learners have to accept the use of cloud computing in their studies. This study endeavours to identify factors that influence the user’s adoption and acceptance of cloud computing in higher education sector. A model derived from a Unified Theory of Acceptance and Use of Technology (UTAUT) model was used to find factors that influence learners to adopt and accept cloud computing during their studies. Results showed that adoption and acceptance of cloud computing were significantly associated with some variables of the UTAUT model except for Effort Expectancy (EE). Performance Expectancy (PE) (p-value= .000), Social Influence (SI) (p-value= .010), Facilitating Conditions (FC) (p-value= .000), Trust (TR) (pvalue= .000), Behaviour Intention (BI) (p-value= .000), and User Behaviour (UB) (p-value= .000). User Behaviour was mostly influenced by Trust, then Facilitating Conditions followed by Performance Expectancy and lastly Social Influence. In conclusion, Trust seems to be the greatest influential factor when it comes to the adoption and usage of applications hosted on the internet.
M (IT) (Department of Information Technology, Faculty of Applied and Computer Science), Vaal University of Technology.
Keywords: Cloud computing; Mobile learning (m-learning); Technology adoption; Unified Theory of Acceptance and Use of Technology (UTAUT); Social influence; Dissertations, Academic -- South Africa.; Cloud computing.; Mobile communication systems in education.; Education -- Higher -- South Africa.